PROPERTY CRIME STATISTICS IN THE KINGDOM OF YUGOSLAVIA - Krstić-Mistridželović, Ivana s; Радовић Стојановић, Јелена (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
The paper analyzes statistical data on property crime in the Kingdom of Yugoslavia in the period from 1924 to 1939. The manner of collecting and publishing data on crime by the General State Statistics of the Kingdom of Yugoslavia, as well as the organization of courts in the Kingdom of Yugoslavia were pointed out. The difference in the way of presenting data on crime in statistical yearbooks according to the legal categorization of criminal offenses is explained as well. The paper presents data on adults and minors convicted by decisions of district and first instance and county courts from 1922 to 1939. The structure of total crime was dominated by crimes against property, and the structure of property crimes was dominated by theft (data from district and first instance courts) and theft and evasion of food and necessities (data from county courts). Such a structure of crime indicates that the causes of property crime were primarily in the difficult economic situation of the population: the crimes of theft, and especially theft and evasion from the trouble of food and necessities were committed primarily due to poverty. This is confirmed by the fact that both total crime and property crime in the Kingdom of Yugoslavia were at the highest level during the World Economic Crisis.
Keywords: crimes against property; crime statistics; statistical yearbooks; Kingdom of Yugoslavia